Competitiveness during Dual-Species Biofilm Formation of Fusarium oxysporum and Candida albicans and a Novel Treatment Strategy - Annarita Falanga; Angela Maione; Alessandra La Pietra; Elisabetta de Alteriis; Stefania Vitale; Rosa Bellavita; Rosa Carotenuto; David Turrà; Stefania Galdiero; Emilia Galdiero; Marco Guida (MDPI AG, 2022)
During an infection, a single or multispecies biofilm can develop. Infections caused by non-dermatophyte molds, such as Fusarium spp. and yeasts, such as Candida spp., are particularly difficult to treat due to the formation of a mixed biofilm of the two species. Fusarium oxysporum is responsible for approximately 20% of human fusariosis, while Candida albicans is responsible for superficial mucosal and dermal infections and for disseminated bloodstream infections with a mortality rate above 40%. This study aims to investigate the interactions between C. albicans and F. oxysporum dual-species biofilm, considering variable formation conditions. Further, the ability of the WMR peptide, a modified version of myxinidin, to eradicate the mixed biofilm when used alone or in combination with fluconazole (FLC) was tested, and the efficacy of the combination of WMR and FLC at low doses was assessed, as well as its effect on the expression of some biofilm-related adhesin and hyphal regulatory genes. Finally, in order to confirm our findings in vivo and explore the synergistic effect of the two drugs, we utilized the Galleria mellonella infection model. We concluded that C. albicans negatively affects F. oxysporum growth in mixed biofilms. Combinatorial treatment by WMR and FLC significantly reduced the biomass and viability of both species in mature mixed biofilms, and these effects coincided with the reduced expression of biofilm-related genes in both fungi. Our results were confirmed in vivo since the synergistic antifungal activity of WMR and FLC increased the survival of infected larvae and reduced tissue invasion. These findings highlight the importance of drug combinations as an alternative treatment for C. albicans and F. oxysporum mixed biofilms.